Demographic factors and risk perceptions at work: how safe do employees feel? - Chang, Joshua; O'Neill, Grant; Travaglione, A. (CCH Australia Limited, 2016)
This report identifies employee demographic profiles based on their risk perceptions of feeling safe from injury and sickness at work. A sample of over 6,000 respondents in the Australian workforce was studied, and a model is presented to illustrate the findings. It was found that employees who were male, aged 25–44, working in the private sector, full-time, short-tenured and non-unionised felt safer from injury and sickness at work, as well as those in managerial, clerical and sales positions. The model presented is expected to provide a predictive and evaluative dimension relating to the management of employee safety, welfare and support.